"Pseudo-Sousveillance": (Re)imagining Immigration Narratives and Surveillance Practices by Experiencing "Use of Force". Issue 2 (1st December 2019) - Marin, Kellie
Abstract : This article introduces the concept of "pseudo-sousveillance" as simulated sousveillance practices created by the sensory environments of immersive technologies. To advance this concept, I analyze the virtual reality (VR) experience "Use of Force" that immerses participants within the scene of the night during which immigrant Anastasio Hernandez Rojas was beaten by border patrol officers at the San Ysidro Port of Entry. I argue that the pseudo-sousveillance practices of cellphone recording and surveillance from above enlist users to be active participants in resisting dominant surveillance practices by constructing alternative narratives about immigrant experiences, exposing the overreach of the border patrol, and revealing the limits of surveillance in immigration control. I then discuss the implications that pseudo-sousveillance has for rethinking the rhetorical power of emerging technologies and sousveillance in a surveillant age.